Analisis Tingkat Kesehatan BPR di Kota Kupang Menggunakan Pendekatan RGEC - Lesly S.O. Fanggidae; Jems A. Zacharias (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2021)
Abstract. This study aims to analyze the soundness level of BPR in Kupang City using the RGEC approach. The population in this study is Rural Banks (BPR) in Kupang City. The sample in this study amounted to 7 BPRs and was selected using a purposive sampling method, namely BPR registered and reporting information on their Financial Statements on the Otoritas Jasa Keuangan website during 2016-2020. The data collection technique in this study used quantitative descriptive methods by collecting data on the publication of BPR financial statements and BPR good corporate governance reports. Based on the results of the analysis and discussion, it can be seen that, generally, the BPR in Kupang City have a very healthy capital aspect. Meanwhile, BPR still needs to pay attention to the completeness of the Good Corporate Governance (GCG) aspect in the form of publication of a good corporate governance report on the BPR website. The GCG aspect is very important for BPRs in giving positive signals to stakeholders that BPRs are managed in a transparent, accountable, responsible, independent and fairness.